2022
DOI: 10.1155/2022/8933442
|View full text |Cite|
|
Sign up to set email alerts
|

Monitoring of Single-Phase Induction Motor through IoT Using ESP32 Module

Abstract: The condition monitoring of rotating machines for critical applications plays an important role in reducing downtime. With Industry 4.0, the role of IoT in online condition monitoring of electrical machines has gained considerable significance. The main aim of the paper is the use of IoT for online monitoring of motor parameters like current, temperature, vibration, and humidity and observing its online trending using a web server. Data can be accessed in form of graphs and widgets by visiting the web page. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The combination of different electric stresses generated through the transient voltages is particularly undesirable [137]. The stator is stressed by thermal, electrical, mechanical, and environmental factors, causing faults [139][140][141]. Table 4 presents the types of fault diagnostics techniques for induction motor (IM) stator faults.…”
Section: Im Stator's Faultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of different electric stresses generated through the transient voltages is particularly undesirable [137]. The stator is stressed by thermal, electrical, mechanical, and environmental factors, causing faults [139][140][141]. Table 4 presents the types of fault diagnostics techniques for induction motor (IM) stator faults.…”
Section: Im Stator's Faultsmentioning
confidence: 99%
“…Table 4 presents the types of fault diagnostics techniques for induction motor (IM) stator faults. The stator is stressed by thermal, electrical, mechanical, and environmental factors, causing faults [139][140][141]. Table 4 presents the types of fault diagnostics techniques for induction motor (IM) stator faults.…”
Section: Im Stator's Faultsmentioning
confidence: 99%
“…Choi et al stated that reduced weight rather than a strong mechanical structure is the key advantage of FSPV systems [20].…”
Section: Development Of the Fspv System And Related Workmentioning
confidence: 99%
“…It was concluded that the system was effective in monitoring the patient's respiration rate and at any instant with abnormal condition, the patient could be given necessary medication. Baqir and Motlak (2021) explored the usability of microcontroller-RF combined Soc having ESP32 Wi-Fi-board to monitor various gases in heat process control (Shukla et al, 2022). The documented results from the system indicated that real-time data were received at the operator platform via Bluetooth Low Energy (BLE) and Wi-Fi, and appropriate decisions based on gas status, and temperature could be decided and sent to the plant side as well using a wireless communication system.…”
Section: Related Workmentioning
confidence: 99%